Real‐time PCR validation of visually identified snapper Chrysophrys auratus (Sparidae) eggs. Issue 2 (28th December 2015) - Dias, P. J.; Wakefield, C. B.; Fairclough, D. V.; Jackson, G.; Travers, M. J.; Snow, M.
Abstract : In this study, a total of 212 eggs were visually identified as snapper Chrysophrys auratus . Real‐time PCR confirmed visual identification in 69% of cases but corroboration varied widely among plankton samples. The use of molecular tools to support visual identification prior to adopting daily egg production stock assessment methods should be considered.